2022
DOI: 10.1021/acsami.2c01019
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Detection and Monitoring of Ionizing Radiation Treatment Using Radiation-Responsive Gel Nanosensors

Abstract: Modern radiation therapy workflow involves complex processes intended to maximize the radiation dose delivered to tumors while simultaneously minimizing excess radiation to normal tissues. Safe and accurate delivery of radiation doses is critical to the successful execution of these treatment plans and effective treatment outcomes. Given extensive differences in existing dosimeters, the choice of devices and technologies for detecting biologically relevant doses of radiation has to be made judiciously, taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…To overcome this limitation, [H 2 L]-SC based hydrogel was fabricated by mixing [H 2 L]-SC , acrylamide (AM), ZnSO 4 , and H 2 O in a glass vial and subsequently adding 4% (wt.) (NH 4 ) 2 S 2 O 8 solution (Figure a). Incubating the mixed precursors at 50 °C for 0.5 h and then cooling them to room temperature afforded [H 2 L]-SC incorporating polyacrylamide gel, namely, [H 2 L]-SC @PAM. Notably, PAM possesses excellent elastic properties and it returns to its original shape without deformation after continuous stretching, compressing, and folding processes (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this limitation, [H 2 L]-SC based hydrogel was fabricated by mixing [H 2 L]-SC , acrylamide (AM), ZnSO 4 , and H 2 O in a glass vial and subsequently adding 4% (wt.) (NH 4 ) 2 S 2 O 8 solution (Figure a). Incubating the mixed precursors at 50 °C for 0.5 h and then cooling them to room temperature afforded [H 2 L]-SC incorporating polyacrylamide gel, namely, [H 2 L]-SC @PAM. Notably, PAM possesses excellent elastic properties and it returns to its original shape without deformation after continuous stretching, compressing, and folding processes (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in radiation therapy it is also very important to control the radiation dose delivered to the patient. Recently, it was reported that the formation of plasmonic gold nanoparticles from gold salts in nanocomposite gels under radiation could be used as a simple dosimeter for the detection of therapeutic levels of radiation [145,146].…”
Section: Radiotherapy and Hadrontherapymentioning
confidence: 99%
“… 167,168 The applicability of the prepared radiation-responsive gel nanosensors to be used as a platform technology for ionizing radiation detection in three different form factors was recently studied, with a view toward diverse clinical use. 169 Ionizing radiation reduces monovalent gold salts in this approach, resulting in the formation of gold nanoparticles within gel matrix formulated in a variety of morphologies such as one-dimensional (1D) needles and two-dimensional (2D) area inserts for multiple modes of brachytherapy, as well as 3D volumetric dose distribution in tissue phantoms. The produced gold nanoparticles can be detected utilizing various but independent means of readout including visual and photothermal detection, which further boosts the adaptability of this approach.…”
Section: Enhancement Of Various Radiation Dosimetry Systems Using Nan...mentioning
confidence: 99%